Retention strategies for health disparities preventive trials: findings from the Early Childhood Caries Collaborating Centers. (19th October 2016) - Garcia, Raul I.; Tiwari, Tamanna; Ramos‐Gomez, Francisco; Heaton, Brenda; Orozco, Mario; Rasmussen, Margaret; Braun, Patricia; Henshaw, Michelle; Borrelli, Belinda; Albino, Judith; Diamond, Courtney; Gebel, Christina; et al.
Abstract: Objectives: To identify successful strategies for retention of participants in multiyear, community‐based randomized controlled trials (RCTs) aiming to reduce early childhood caries in health disparities populations from diverse racial/ethnic backgrounds and across diverse geographic settings. Methods: Four RCTs conducted by the Early Childhood Caries Collaborating Centers (EC4), an initiative of the National Institute of Dental and Craniofacial Research, systematically collected information on the success of various strategies implemented to promote participant retention in each RCT. The observational findings from this case series of four RCTs were tabulated and the strategies rated by study staff. Results: Participant retention at 12 months of follow‐up ranged from 52.8 percent to 91.7 percent, and at 24 months ranged from 53.6 percent to 85.9, across the four RCTs. For the three RCTs that had a 36‐month follow‐up, retention ranged from 53.6 percent to 85.1 percent. Effectiveness of different participant retention strategies varied widely across the RCTs. Conclusions: Findings from this case series study may help to guide the design of future RCTs to maximize retention of study participants and yield needed data on effective interventions to reduce oral health disparities.